Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
y = -15
x = -10
Step-by-step explanation:
1/4x - 1/2 = 5 (1)
3x + 2/3y = -40 (2)
Multiply (1) by 4
1/4x - 1/2 = 5
1/4x * 4 - 1/2y * 4 = 5 * 4
4/4x - 4/2y = 20
x - 2y = 20 (3)
Multiply (2) by 3
3x + 2/3y = -40 (2)
3x * 3 + 2/3y * 3 = -40 * 3
9x + 6/3y = -120
9x + 2y = -120 (4)
x - 2y = 20 (3)
9x + 2y = -120 (4)
Using elimination method, Add (3) and (4)
9x + x = -120 + 20
10x = -100
x = -100/10
x = -10
Substitute x = -10 into (3)
x - 2y = 20 (3)
-10 - 2y = 20
-2y = 20 + 10
-2y = 30
y = 30/-2
y = -15
y = -15
x = -10
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.